The inter linkage of corporate reputation between corporate social responsibility and financial performance - Muzammal Ilyas Sindhu; Muhammad Arif (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
Many researchers confirm that corporate social responsibility (CSR) has a direct and indirect influence on financial performance. This study examines the mediating effect of corporate reputation between the relationship of corporate social responsibility and financial performance in Pakistan's banking sector. Structural equation modeling has been applied to explore this relationship and the primary data are collected using developed scale. The findings are based on 405 responses from bank employees and the results show that corporate social responsibility significantly influencing financial performance and this relation is partially mediated by customer satisfaction, corporate reputation, and competitive advantage. These results also suggest an increment in CSR activities that enhance financial performance by indirectly targeting the aforementioned intangible assets.
Keywords: 330; corporate social responsibility (CSR); financial performance; customer satisfaction; corporate reputation; competitive advantage